Analisis Kepuasan Pasien Terhadap Kualitas Pelayanan Rawat Jalan Rumah Sakit X Menggunakan Service Quality Metode Costumer Statisfaction Index (CSI) dan Importance Performance Analysis (IPA) - Saputri, Anggi Lisa; Lubis, Fitriani Surayya; Suherman, Suherman; Nazaruddin, Nazaruddin; Nur, Muhammad (Universitas Batanghari Jambi, 2024)
This study aims to evaluate the level of customer satisfaction with outpatient services at Hospital X and identify areas that require improvement. The results of data processing show that the customer satisfaction index (CSI) value obtained is 76.435%, which is included in the